The Role of Technological Innovation in Community Development (a case study on Implementation of Application SIDEKEM on Pemalang District) - Yuliana Kristanto; Amni Zarkasyi Rahman (Journal of Public Administration and Local Governance, 2018)
Government Regulation No. 72 in 2005 about Government Villages implied that the role of national development within the village currently has a vital role. One of the essential elements required of the village is the village information system. One example that has been put into practice is Pemalang District successfully developed application systems information village (SID) that is named SIDEKEM. This innovation was even recognized by the international arena with the award he received Champion Award from the ITU (Information Technology Union) saplings organization UNESCO-UN/PBB) by Regent of Pemalang. SIDEKEM that was originally aimed at facilitating administrative services at the village community, it also managed to move the village economy and changing social paradigm that had long existed. In this example of cases studies of implementation of SIDEKEM in one of the model village is at Penggarit Village. This village is via SIDEKEM successfully introduced the yield potential of growing and creating new jobs opportunity. It is aligned with the theory of community development, a process which is a community effort own are integrated with government authorities to improve the socio-economic conditions and cultural community, integrate the community into the national life and encourage the contribution of the community to a more optimal for national progress (Hayden 1979:175). Surely in practice always find some barriers. But SIDEKEM in all of its limitations has managed to push changes in the community at Penggarit Village.   Keywords: Village Community; System Information Village; SIDEKEM; Pemalang District; Community Development